Stewarding Water in the Great Economy - Bader-Saye, Scott (Anglican theological review, 2018)
This article uses the Christian metaphor of stewardship to address the growing and unprecedented crisis of fresh water scarcity. Stewardship provides a way of naming a theological vision of responsibility for what is not our own. At the same time the metaphor resonates with non-theological accounts of responsibility, allowing a common framework for Christians and non-Christians to engage together in local and global problem solving. Faithful stewardship requires the use of prudence to discern the hierarchy of goods served by water, as well as the means by which the distribution and availability of water can be managed justly for the sake of the flourishing of creation. The article also addresses the potential dangers of the stewardship metaphor and suggests that stewardship is best understood as the wise tending of a little economy within what Wendell Berry calls the "Great Economy," or the kingdom of God.